2019
DOI: 10.1111/jwas.12670
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein reduction for Nile tilapia fingerlings reared in biofloc technology

Abstract: The objective of this study was to evaluate the growth performance of Nile tilapia fed diets with 28, 32, and 36% crude protein (CP) in biofloc technology (BFT) and to verify its influence on water quality and hematological parameters.The experimental design was completely randomized with three treatments (28, 32, and 36% CP) and six replicates.Nile tilapia (n = 270, 6.31 ± 0.40 g) were randomly distributed in 18 aquaria-200 L (15 fish/aquarium), over a period of 60 days. No differences (p > .05) were observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 29 publications
0
12
0
3
Order By: Relevance
“…The availability of balanced protein diet (biofloc) and stress free environment (lower nitrite and ammonia) may be the major reason for the growth performance of GIFT compared to a high CP supplementary diet in the biofloc Effect of Distillery Spent Wash as Carbon Source in Biofloc System on Nutrient Profile of GIFT Tilapia system. According to Hisano et al (2020), tilapia have been feeding with 36, 32 and 36% of CP diet in nursery BFT (sugar cane molasses used as carbon source) and no significant difference was observed in terms of growth performance among treatments, but, the author suggested that 28% of CP reduced the feed cost and environmental impact. Floc encompassed low crude lipid and high crude fibre.…”
Section: Resultsmentioning
confidence: 99%
“…The availability of balanced protein diet (biofloc) and stress free environment (lower nitrite and ammonia) may be the major reason for the growth performance of GIFT compared to a high CP supplementary diet in the biofloc Effect of Distillery Spent Wash as Carbon Source in Biofloc System on Nutrient Profile of GIFT Tilapia system. According to Hisano et al (2020), tilapia have been feeding with 36, 32 and 36% of CP diet in nursery BFT (sugar cane molasses used as carbon source) and no significant difference was observed in terms of growth performance among treatments, but, the author suggested that 28% of CP reduced the feed cost and environmental impact. Floc encompassed low crude lipid and high crude fibre.…”
Section: Resultsmentioning
confidence: 99%
“…(2020) and Hisano et al. (2020) in BFT‐based tilapia culture. TSS (589 mg/l) and BOD (8.4 mg/l) values of the present study were superior than the study of Caipang et al.…”
Section: Discussionmentioning
confidence: 98%
“…Long‐term studies can highlight the differences between treatments. In addition, the BFT system may have positive effects on fish performance (Hisano et al, 2019; Da Silva et al, 2018) and may have masked the effects of treatments. The relationship between fermented products and production systems still needs to be better studied and understood.…”
Section: Discussionmentioning
confidence: 99%